Identifying physiological processes limiting genetic improvement of ear fertility in wheat - Gaju, Oorbessy (2007)
Wheat (Triticum aestivum L.) is one of the three most important cereal crop grown globally and there is a gap between yield production and world demand. Previous studies on wheat have generally shown traits influencing the capacity of the grains to store assimilate (sink) to be better correlated with yield than traits influencing potential assimilate production (source). Therefore, strategies to improve ear fertility, defined as the number of grains per ear, are one of the most relevant features in the development of new cultivars and genetic improvement of yield potential. In the present study, novel large-ear phenotype (long rachis) is investigated as a trait to increase the number of grains per year, thus grains m", with the aim of identifying physiological processes limiting genetic improvement of ear fertility in wheat. Two advanced lines (NLI and NL2) developed by the International Centre for Maize and Wheat Improvement (CIMMYT) with novel ear morphology and one CIMMYT cultivar with conventional ear morphology Bacanora referred to as the parental spring wheat genotypes were characterized. In addition, 69 doubled-haploid (DR) lines from a cross between NL2 x Rialto (UK-bred cultivar) were used to investigate the physiological basis of improved ear fertility and yield potential in the novel material. Three field experiments were carried out at the CIMMYT experimental station in Cd. Obregon (Mexico) on the parental genotypes (2003/04, 2004/05 and 2005/06) while two field experiments were carried out for the NL2 x Rialto population (2004/05 and 2005/06). An additional experiment consisting of a subset of 15 lines of the NL2 x Rialto population was carried out in 2005/06. Two controlled-environment experiments were carried out at Sutton Bonington, University of Nottingham in 2004 and 2005 to investigate the developmental basis of the large-ear phenotype on the three parental genotypes. A post-anthesis (GS 61+ 14d) degraining treatment was imposed in field experiments examining the parental genotypes in 2004, 2005 and 2006 while a similar degraining treatment was carried out for the subset of 15 DR lines of the NL2 x Rialto population in 2006. A range of physiological traits related to ear fertility were measured on the parental genotypes and the DR lines including rachis length, spikelets ear"1, developmental stages, green area, radiation interception, radiation use-efficiency (RUE), dry matter production and partitioning, stem water soluble carbohydrate reserves, potential grain weight, grain weight and combine yield. In the growth-room experiments, the rate and duration of spikelet primordial production of the main shoots were measured. Present results showed that in the novel genotypes, longer rachis increased spikelets ear" and also grains ear-i. Thus, the novel genotypes showed greater ear fertility by having more grains ear" than the benchmark cultivar Bacanora. Grains m-2 was not actually increased in novel genotypes; indeed lower grains m-2 was found in NL2 compared to Bacanora. Heavier grains were found in the novel genotypes which had greater potential and final grain weight compared to Bacanora. The NL2 genotype possesses a tiller inhibition gene (tin) on chromosome 1A and this genotype had fewer ears m-2 than the other genotypes, and this trait also contributed to the lower grains m-2 ofNL2. The grains-to-ear DM ratio at GS 61 in NL2 was markedly lower compared to other genotypes. Results of the growth-room experiments showed that there was a developmental basis for the higher spikelets ear" observed in NLl and NL2 than Bacanora. A longer thermal duration from floral initiation to terminal spikelet was associated with a higher spikelet number in NL1 (27) and NL2 (29) compared to Bacanora (23). Since the growth-room experiments were carried out under long photoperiod (16 hrs) results also suggested that the large-ear phenotype may have been associated with the effects of 'earliness per se' genes. Grain weight of the parental genotypes did not respond differently to degraining. Averaging across parental genotypes and years, responses to degraining in the field experiments showed that although assimilate supply per grain was potentially increased by 100%, average grain weight was only increased by 15%. These findings indicated that grain yield was mainly limited by post-anthesis sink size in these experiments. In the subset of 15 DH lines experiment, there were different responses of the lines to degraining and the lines which showed larger responses of individual grain weight to degraining had lower grain weight in control intact ears. Results of the DH experiments showed that rachis length was positively correlated with spikelets ear", grains ear" and grains m-2 among the lines. There was also a positive phenotypic correlation between the grains-to-ear DM ratio at GS 61 and grains m-2 amongst the lines. However, the large-ear phenotype (long rachis, high spikelets ear") was not associated with greater grain yield due to a trade-off between grains m-2 and individual grain weight. The physiological mechanisms potentially explaining this trade off are analyzed. Harvest biomass was positively correlated with grain yield amongst the DH lines. So traits to improve biomass whilst maintaining harvest index may be important for future breeding. Present results showed a positive correlation between pre-anthesis RUE and harvest biomass amongst the subset of 15 lines of the NL2 x Rialto DH population. It is suggested that breeders might select for higher RUE (via high specific leaf weight) to improve grains m-2 and yield potential in future years.